2004
DOI: 10.1270/jsbbs.54.351
|View full text |Cite
|
Sign up to set email alerts
|

CMA Banding Pattern of Chromosomes Is Useful for the Identification of Chromosome Doubling in Haploid Citrus

Abstract: A variant plant showing long internodes arose from a haploid plant obtained from clementine (Citrus clementina). Flow cytometric analysis and chromosome count revealed that it was a mixoploid with both haploid (2n = x = 9) and diploid (2n = 2x = 18) cells. The average length of the guard cells of the variant was almost the same as that of the haploid plant. This suggested that the epidermis of the variant consisted of haploid cells and that other leaf tissues consisted of diploid cells. Since in citrus the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Duplication of the chromosome stock of nucellar cell-producing embryos is frequent in apomictic diploid plants of citrus [ 60 ]. However, it is rare in somatic vegetative tissue of diploid plants [ 61 ] although Yamamoto and Tominaga [ 62 ] obtained a haploid-diploid periclinal chimera from a haploid plant recovered in a cross between clementine and a triploid hybrid. This double haploid line is still young and, therefore has not been characterized yet from the reproductive point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication of the chromosome stock of nucellar cell-producing embryos is frequent in apomictic diploid plants of citrus [ 60 ]. However, it is rare in somatic vegetative tissue of diploid plants [ 61 ] although Yamamoto and Tominaga [ 62 ] obtained a haploid-diploid periclinal chimera from a haploid plant recovered in a cross between clementine and a triploid hybrid. This double haploid line is still young and, therefore has not been characterized yet from the reproductive point of view.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for many years that contrary to initial expectations, the plants derived from the various in vitro techniques are not all haploid and that a range of ploidies, including ploidy chimaeras (Yamamoto and Tominaga, 2004), can be generated. A good example of this is provided by an analysis of microspore‐derived plants regenerated from cultured anthers of Datura innoxia .…”
Section: In Vitro Induction Of Haploidsmentioning
confidence: 92%
“…In previous studies (Germana and Chiancone, 2003;Germana et al, 1994Germana et al, , 2000, isozyme, RAPD, and microsatellite analysis were used for the identifi cation of doubled haploids in Citrus. Recently, a combination of enzymatic maceration and fl uorescent staining, such as CMA and/or 4´-6-diamidino-2-phenyl-indole (DAPI), has been used for identifying Citrus chromosomes and has been applied for biotechnological studies such as genome analysis, somatic hybridization, and ploidy manipulation (Befu et al, 2000;Guerra, 1993;Miranda et al, 1997aMiranda et al, , 1997bYahata et al, 2005b;Yamamoto and Tominaga, 2004;Yang et al, 2002). By CMA staining of the chromosomes, Yamamoto and Tominaga (2004) demonstrated that diploid cells in a haploid-diploid periclinal chimera were doubled haploid cells arisen from a haploid plant obtained from clementine.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, a combination of enzymatic maceration and fl uorescent staining, such as CMA and/or 4´-6-diamidino-2-phenyl-indole (DAPI), has been used for identifying Citrus chromosomes and has been applied for biotechnological studies such as genome analysis, somatic hybridization, and ploidy manipulation (Befu et al, 2000;Guerra, 1993;Miranda et al, 1997aMiranda et al, , 1997bYahata et al, 2005b;Yamamoto and Tominaga, 2004;Yang et al, 2002). By CMA staining of the chromosomes, Yamamoto and Tominaga (2004) demonstrated that diploid cells in a haploid-diploid periclinal chimera were doubled haploid cells arisen from a haploid plant obtained from clementine. In the present study, we could also easily identify that the diploid strain was the complete doubled haploid of a haploid from ʻBanpeiyuʼ pummelo by using CMA staining.…”
Section: A B Cmentioning
confidence: 99%